Prevalence of Cytomegalovirus in Patients With Multiple Sclerosis: A Case-Control Study in Northern Iran - Najafi, Saeideh (Jundishapur J Microbiol, 2016)
BACKGROUND: Multiple sclerosis (MS) is a chronic debilitating disease known as one of the most common neurological dysfunctions in young adults. Recent studies suggest that infections with herpesviruses play a critical role in the pathogenesis of MS. OBJECTIVES: The present investigation aimed to detect the presence of cytomegalovirus (CMV) in patients with MS using polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) methods. PATIENTS AND METHODS: Plasma and peripheral blood mononuclear cells (PBMCs) were collected from MS patients (n = 82) and from blood donors as control group (n = 89). They were tested for the presence of CMV antibodies and DNA by ELISA and PCR, respectively. RESULTS: Anti-CMV was positive in 65 (79.3%) and 69 (77.5%) of the MS patients and healthy subjects, respectively (P= 0.853). Similarly, 23 (28%) and 2 (2.2%) patients were positive for CMV DNA among the MS and control groups, respectively. Statistical analysis showed that the frequency of CMV DNA in the MS patients was significantly higher than in the healthy controls (P < 0.001). CONCLUSIONS: The results of this study showed a possible association between CMV infection and MS. Further experimental and epidemiological studies using case-control approaches are needed to confirm this association.